Effectiveness of mindfulness-based online therapy or internet-delivered cognitive behavioral therapy compared with treatment as usual among patients with persistent somatic symptoms: Protocol for a randomized controlled trial. - Velina Vangelova-Korpinen; Helena Liira; Samu N Kurki; Markku Sainio; Antti Malmivaara; Mari Kanerva; Jan-Henry Stenberg; Mikko Varonen; Mikko Venäläinen; Piia Vuorela; Jari Arokoski (PLoS ONE)
Background Persistent somatic symptoms unexplained by a defined medical or psychiatric condition often include a component of central sensitization. Many treatment options are based on cognitive behavioral therapy. Effective widely available therapies are scarce. There are self-management programs and e-therapies that aim at overcoming the central sensitization by modifying interoceptive neural networks in the brain. Objectives This study aims to investigate the effect of a mindfulness-based amygdala and insula retraining (AIR) online program and an internet delivered therapist assisted therapy offered by Helsinki University Hospital (HUS iCBTpss) compared to treatment as usual (TAU) in the treatment of conditions causing persistent somatic symptoms. Methods We will perform a randomized controlled trial aiming at 360 patients. Consenting patients will be randomized to three study arms: online AIR program, HUS iCBTpss (both interventions as add-ons to TAU); and TAU. Functional ability and quality of life surveys will be collected from participants at baseline and at 3, 6, and 12 months after entering the study. Conclusions This study is one of the first to explore non-drug based online interventions developed to overcome the brain's central sensitization and are available and accessible to patients both in primary and secondary care. The results will develop the management of the common, often debilitating persistent somatic symptoms related to many conditions unexplained by a defined somatic or psychiatric illness. Trial registration number NCT05212467.